Pengaruh Penggunaan Facebook Pada Pembelajaran dengan Model Problem Posing terhadap Hasil Belajar Stoikiometri - Shinta Amalia (Kayon Media, 2019)
The purpose of this study was to find out: (1) differences in cognitive learning outcomes between students who use the problem posing learning model accompanied by discussion through Facebook and without Facebook; (2) the quality of questions formulated by students using the problem posing learning model accompanied by discussion through Facebook and without Facebook. This research uses quasi-experimental research design. The research sample consisted of 2 classes chosen randomly. Both classes use problem posing models in stoichiometry learning. The results showed: (1) the cognitive results of students in learning posing problems accompanied by discussions through Facebook were better than the cognitive results of students in learning posing problems accompanied by discussions without facebook; (2) there is no difference inTujuan penelitian ini adalah untuk mengetahui: (1) perbedaan hasil belajar kognitif siswa antara yang menggunakan model pem-belajaran problem posing disertai diskusi melalui facebook dan tanpa facebook; (2) kualitas soal yang dirumuskan siswa antara yang menggunakan model pembelajaran problem posing disertai diskusi melalui facebook dan tanpa facebook. Penelitian ini menggunakan rancangan penelitian eksperimen semu. Sampel penelitian terdiri dari 2 kelas yang dipilih secara acak. Kedua kelas menggunakan model problem posing dalam pembelajaran stoikiometri. Hasil penelitian menunjukkan: (1) hasil kognitif siswa dalam pembelajaran problem posing disertai diskusi melalui facebook lebih baik dibandingkan hasil kognitif siswa dalam pembelajaran problem posing disertai diskusi tanpa facebook; (2) tidak ada perbedaan kualitas soal yang dirumuskan siswa pada kedua kelas.